Millet, Wheat, and Society in North China over the Very Long Term. (1st February 2021) - He, Hongzhong; Lawson, Joseph; Bell, Martin; Hui, Fuping
Abstract : This paper outlines a very longue durée history of three of North China's most important cereal crops: broomcorn millet, foxtail millet, and wheat. It illustrates their place within broader social-environmental formations, highlighting the various biological and cultural factors that enabled the spread of these crops, as well as the ways in which these crops and the patterns in which they are grown influenced North China's economic and social history. We demonstrate that a very long-run approach raises new questions and clarifies the significance of particular transitions. The article charts the transition from broomcorn to foxtail millet cultivation in the late Neolithic, and then the rise of wheat in the first millennium ce. It shows that efforts to spread winter wheat met some resistance from farming communities, and presents the hypothesis that the different processing technologies for wheat and millet may have played a role in the divergence of different Eurasian societies. Finally the article considers the debate over the spread of multiple-cropping systems to North China.